Acute intestinal obstruction in systemic lupus Erythematosus: Case report and review of the literature - Bouali Mounir; Eddaoudi Yassine; El Wassi Anas; El Bakouri Abdelilah; El Hattabi Khalid; Bensardi Fatimazahra; Fadil Abdelaziz (Global Journal of Rare Diseases - Peertechz Publications, 2023)
Introduction: Gastrointestinal manifestations in systemic lupus erythematosus are common and may involve any segment of the digestive tract. Lupus enteritis is one of the manifestations responsible for abdominal pain. Its treatment is based essentially on corticosteroids. The use of immunosuppressive drugs is reserved for recurrent forms or in case of failure of corticosteroids. Materials and methods: We report a case of "acute intestinal obstruction in systemic lupus erythematosus" in the Department of Emergency visceral surgery. Results: Mrs. SQ, S, 24 years old, was diagnosed one week ago with systemic lupus erythematosus at the beginning of treatment, with a history of pancreatitis stage E, history of current illness goes back to 05 days before her admission by the installation of a sub-occlusive syndrome made of cessation of matter and gas associated with food vomiting, with cessation of matter and gas in the last 48 hours. Para-clinical The Abdomen without preparation showed hydroaeric levels. With an abdominal CT scan which showed: CT scan appearance in favor of bowel obstruction with evidence of a transitional level above the umbilical: inflammatory stenosis? The spontaneously hyper-dense appearance of the colonic lumen and some ileal intestines is most probably related to a digestive hemorrhage that could be part of lupus enteritis given the patient's past history with the spontaneously hyper-dense appearance of the colonic lumen and ileal intestines most probably related to a digestive hemorrhage. And distension of the jejunal and some ileal coves, measuring: 36mm in maximum diameter, the seat of hydrophobic level with a transitional level above umbilical. Significant gastric distension. No parietal pneumatosis with no parietal enhancement defect. In view of the clinical symptomatology and the CT scan results, the patient underwent an exploratory laparotomy with the following findings: Absence of peritoneal effusion with the presence of a 3 cm distension of the bowel without any sign of flange, stenosis, or detectable obstacle, with the performance of multiple biopsies at the level of the greater omentum, the mesentery, and the anterior parietal peritoneum Conclusion: Intestinal pseudo-obstruction is a rarely reported manifestation during systemic lupus erythematosus. It is a rare but potentially serious manifestation that can reveal the disease or occur during the course of the disease. The use of immunosuppressive drugs is reserved for recurrent forms or in case of failure of corticosteroids. However, recurrences are frequent. Azathioprine is an alternative therapy to control the disease. However, recurrences are frequent. Azathioprine is an alternative therapy to control the disease.